Karakteristik Biota Perairan dan Kondisi Lingkungan sebagai Dasar Pengelolaan Sumber Daya Perikanan di Ekosistem Mangrove Mangkang Wetan, Semarang - Kennedi Sembiring; Miftu Khoerunnisa; Arief Baswantara (Jurnal Manajemen Pesisir dan Laut, 2026)
Mangrove ecosystems are highly productive coastal habitats and play an important role in supporting the sustainability of fisheries resources through their function as spawning, nursery, and feeding areas for various aquatic biota. However, environmental pressures and anthropogenic activities have the potential to degrade habitat quality and affect the community structure of biota associated with mangroves. The main problem in this study is the limited information regarding the relationship between the community structure of aquatic biota and environmental factors in the Mangkang Wetan mangrove ecosystem as a basis for ecosystem-based fisheries management. This study aims to analyze the community structure of aquatic biota associated with mangroves and their relationship with environmental factors. The method used is purposive sampling at three stations representing the coastal, transition, and estuarine zones. Biota data were collected through Visual Encounter Survey (VES) and identified morphologically, while environmental parameters include temperature, water and soil pH, salinity, and substrate characteristics. The results showed that the true mangrove found was Avicennia marina, with seven genera of associated biota from the classes Gastropoda, Malacostraca, and Actinopterygii. The diversity index (H′) values ranged from 0.938 to 1.303, with the highest values at sandy and high-salinity stations. Association analysis showed a strong relationship between Avicennia marina and Telescopium sp. and Cerithidea sp. (OI = 0.88). Salinity and substrate type were the main factors influencing the distribution of biota. These findings indicate that the ecosystem is still ecologically functional, but there are indications of species homogeneity and environmental stress. Therefore, ecosystem-based management is needed through mangrove conservation and controlling human activities